Appropriateness Criteria for Choosing Proper Risk Assessment Model of Nanomaterial Manufacturing Processes - Mostafa Dadkhah, Seyyed; Golbabaei, Farideh; Malakootikhah, Javad; Mohamadfam, Iraj (Asian Journal of Chemistry, 2012)
The importance of risk identification and assessment of manufacturing processes is well known and it is doubled for unknown products and technologies such as nanotechnology. Whensoever a new technology is offered there are major concerns regarding its potential risks and hazards. So many methods like CHECK LIST, FMEA (Failure modes and effect analysis) and FTA (fault tree analysis) have been yet proposed for risk assessment in the industries, each, in turn, is effective in particular cases. The question is now what kind of technical, social and organizational parameters should be considered through selecting proper model for nanotechnology risk assessment. Study ahead, aims at determining the role of parameters involved in selecting appropriate risk assessment model of nanomaterial manufacturing processes. Accordingly, by examination of all features of common risk assessment methods listed in ISO31000 as well as the opinions of expertise, a pattern was recommended for choosing proper risk assessment model in nanomaterial manufacturing processes. The statistic society was all the active manufacturers of nanomaterials participated at The Third International Festival and Exhibition on Nanotechnology held on November 28, 2010 in Iran. The obtained results indicated that due to the small size of production units of nanomaterials and lack of being organized in such production units, the research hypothesis was rejected for the statistic society. Therewith, presenting an identification model for proper risk assessment methods of nanomaterials manufacturing process were considered meaningless regarding to the current circumstance.